URBAN MOBILITY: a case study in the central region of Jaboticabal/SP - Augusti, Natália Carolina; Ascanio, Elisandra; Pereira, Gleison Luiz Arruda; Pereira, André Luiz Arruda; Mendes, Oswaldo Lázaro (Revista Interface Tecnológica, 2020)
This article aims to evaluate urban mobility in the central region of Jaboticabal. In this way, for its development, a research was carried out to ponder what the population's view of the study region was, subsequently the traffic lights were monitored, and used the ARENA simulation software. With the use of the ARENA software, several simulations were carried out until it was possible to find a time for the traffic light that would allow better synchronism, enabling the green wave which makes it possible to decongest the traffic in the region and consequently improves the quality of life of the residents of the city that frequent the studied region.